2013
DOI: 10.1002/ajhb.22423
|View full text |Cite|
|
Sign up to set email alerts
|

Reliability of standard circumferences in domain‐related constitutional applications

Abstract: This study suggests the appreciation of the waist circumference. This measure is not valid for lean individuals, but might be for the obese. It is suggested likewise that a combination of chest and hip circumference may have a more general application within the public health sector. In summary, evidence confirms the reliability of a series of circumferences but creates doubts or rejects other colloquially established perimeters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
1
15
0
3
Order By: Relevance
“…In human cadaver studies, maximal calf circumference has been shown to be highly correlated with total muscle mass among Brussels male cadavers ( r = 0.84) . Maximal calf circumference was also highly correlated with muscle mass both at segmental ( r = 0.95) and total ( r = 0.90) levels among Caucasian male cadavers, whereas among the females, the correlation coefficients were not as high for muscle mass at segmental ( r = 0.67) and total ( r = 0.77) levels . Rolland et al .…”
Section: Discussionmentioning
confidence: 97%
“…In human cadaver studies, maximal calf circumference has been shown to be highly correlated with total muscle mass among Brussels male cadavers ( r = 0.84) . Maximal calf circumference was also highly correlated with muscle mass both at segmental ( r = 0.95) and total ( r = 0.90) levels among Caucasian male cadavers, whereas among the females, the correlation coefficients were not as high for muscle mass at segmental ( r = 0.67) and total ( r = 0.77) levels . Rolland et al .…”
Section: Discussionmentioning
confidence: 97%
“…In a study concerning the reliability of standard circumferences in domain-related constitutional applications, the CC was strongly connected with the muscle mass rather than the fat mass at the segmental and total levels [33]. An earlier study conducted by Rolland, noted that the CC was positively associated with the dual-energy x-ray absorptiometry (DEXA)-measured appendicular skeletal muscle mass (ASM) in elderly subjects aged at least 70 years [34].…”
Section: Discussionmentioning
confidence: 99%
“…Na avaliação das medidas antropométricas segundo o gênero, as idosas apresentaram médias mais elevadas em relação aos homens, em medidas de obesidade geral (IMC), de obesidade central (CC e CQ, RCE e relação DAS/Estatura) e em medidas de reserva adiposa (dobras cutâneas, média de seis dobras cutâneas, CB e AGB) associadas a risco cardiovascular e desordens metabólicas [42].…”
Section: Discussionunclassified
“…Estudos avaliando medidas de circunferência do punho e CAB em relação ao gênero não foram localizados, talvez por serem perímetros com evidên-cias biológicas ainda não tão bem estabelecidas [42]. Entretanto, já há registro na literatura de que alterações na CAB podem estar associadas à força de preensão palmar, principalmente entre os homens [61], o que…”
Section: Discussionunclassified
See 1 more Smart Citation